1997
DOI: 10.1111/j.1469-7793.1997.041bo.x
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of phorbol esters on transmitter release and calcium currents at frog motor nerve endings

Abstract: Phorbol esters activate protein kinase C (PKC) and also increase the secretion of neuro‐transmitter substances by an unknown mechanism. To evaluate whether the stimulatory effects of such agents on acetylcholine (ACh) secretion occur as a consequence of stimulation of Ca2+ entry, we made electrophysiological measurements of ACh secretion (i.e. endplate potentials, EPPs) and the component of the prejunctional perineural voltage change associated with nerve terminal calcium currents (perineural calcium current) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 27 publications
5
56
0
Order By: Relevance
“…This view is supported by a number of studies in which pharmacological effects of phorbol esters and other PKC-directed drugs could not be correlated with PKC function (e.g. Scholfield and Smith, 1989;Fabbri et al, 1994;Simon et al, 1996;Redman et al, 1997;Stevens and Sullivan, 1998;Hori et al, 1999;Honda et al, 2000;Iwasaki et al, 2000;Waters and Smith, 2000). More recently, several studies provided direct evidence for the functional importance of the regulation of four non-PKC DAG/phorbol-ester receptors by DAG and phorbol esters in distinct cellular processes.…”
Section: Non-pkc C1 Domain Proteinssupporting
confidence: 48%
“…This view is supported by a number of studies in which pharmacological effects of phorbol esters and other PKC-directed drugs could not be correlated with PKC function (e.g. Scholfield and Smith, 1989;Fabbri et al, 1994;Simon et al, 1996;Redman et al, 1997;Stevens and Sullivan, 1998;Hori et al, 1999;Honda et al, 2000;Iwasaki et al, 2000;Waters and Smith, 2000). More recently, several studies provided direct evidence for the functional importance of the regulation of four non-PKC DAG/phorbol-ester receptors by DAG and phorbol esters in distinct cellular processes.…”
Section: Non-pkc C1 Domain Proteinssupporting
confidence: 48%
“…However, in spite of relatively high concentrations, the blocking effect of PKC inhibitors was incomplete, implying that there may be an additional mechanism mediating the effect of phorbol ester. While an involvement of PKC in the PESP has been suspected (Scholfield and Smith, 1989;Redman et al, 1997), it was recently reported that phorbol esters or DAG stimulates the vesicular protein Doc2␣ to interact with the plasma membrane-associated protein Munc13-1 (Orita et al, 1997). The N-terminal domain (Mid) of Doc2␣ is involved in this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no direct evidence to indicate which, if any, of the above targets are involved in the phorbol ester-induced synaptic potentiation (PESP). Furthermore, an involvement of PKC in the PESP has been questioned recently at some synapses, where certain PKC inhibitors had no effect on the PESP (Redman et al, 1997). It has been reported that Munc13-1, a mammalian homolog of Caenorhabditis elegans unc13p, has a diacylglycerol (DAG) receptor similar in affinity to PKC and is localized in the plasma membrane near the release site (Betz et al, 1998).…”
Section: Abstract: Phorbol Ester; Synaptic Facilitation; Doc2␣; Muncmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of H-7 to the solution containing CCPA did not modify the effect of the A 1 analog on mepp frequency (55.671.9% of control values, n ¼ 4, Figure 4b). On the other hand, if stimulation of PKC is the reason for inactivation of Ltype VDCCs, 200 nM PMA, a phorbol ester known to activate PKC at neuromuscular junctions (Shapira et al, 1987;Redman et al, 1997;Angleson & Betz, 2001), would occlude…”
Section: Mechanism Of Action Of Ccpa On L-type Vdccsmentioning
confidence: 99%